A Systematic Review of Clinical Outcomes of Pedicled Flap Repairs of the Knee Extensor Mechanism - Lee, Nayun; Fisher, Marlie H.; McNamara, Colin T.; Greyson, Mark A.; Hogan, Craig A.; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2024)
Background Rupture of the extensor mechanism of the knee has severe functional morbidity, and repair can be complicated by infection, allograft degeneration, and recurrent rupture. Techniques of autologous tissue repair utilizing pedicled flaps such as the gastrocnemius offer vascularized methods of reconstruction, with potentially diminished complication rates. The goal of this study was to evaluate the functional outcomes and complications associated with pedicled flap repair of the knee extensor mechanism.Methods A systematic review was conducted following the Preferred Reporting Items for Systemic Reviews and Meta-Analyses guidelines. Publications that focused on local myocutaneous flaps as a means for reconstruction were included. Causes for knee extensor mechanism deficit, flap characteristics, ambulation rate, changes in range of motion pre- and postoperation, and postoperative complications were analyzed. Technique reports including primary suture repairs, synthetic mesh, and allograft use were excluded.Results An initial 119 studies were identified, with final review of 22 observational studies encompassing 128 cases of pedicled flap reconstructions. The gastrocnemius (88.2%, n = 113), quadriceps (6.3%, n = 8), and a combination of the vastus and gastrocnemius flaps (5.5%, n = 7), were the most frequently utilized flaps. Functional outcomes were favorable with 87.2% of patients achieving ambulation without external support. Variability in range of motion outcomes across different flap may be secondary to the patient characteristics as well as extent of initial injury.Conclusion Autologous pedicle flap reconstruction of the knee extensor mechanism emerges as a viable option for cases characterized by extensive defects and insufficient soft tissue coverage, which are not amenable to direct suture repairs or allografts. Postoperative assessments revealed that the majority of patients experienced improved ambulation status, with no instances of deterioration noted among the patients.
Keywords: knee extensor; local flap; gastrocnemius; patellar tendon